SIMULASI NUMERIK DESAIN CRADDLE DECK DERMAGA KAPAL 150 GT - Mohammad Sholikhan Arif; Heri Supomo; Triwilaswandio W. Pribadi; Sufian Imam Wahidi; Rizky Chandra Ariesta; Sri Rejeki Wahyu Pribadi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Cradle is a lifting tool used to transport ships. The innovation of the cradle design as a deck tool for transporting ships to the dock is a breakthrough to simplify the transportation process. Of course, in the design process, a method is needed to get a design that meets the standard. Numerical simulation is a method that is applied to determine the stress that occurs in the cradle when it is subjected to a load. The workload is a ship transported with the assumption that the load is evenly distributed along with the cradle. The design acceptance criteria were chosen based on the ability of the cradle structure to withstand axial and transverse loads. The standard code as a reference uses the allowable stress criteria from the Indonesian Classification Bureau (BKI) in each local stress. Based on the simulation results, it is found that the sluggishness of the planned cradle design is able to withstand the workload so that the cradle design is feasible to be applied to the operational process.